Cut-off points for isometric handgrip and low limb explosive strength in relation to indicators of overweight/obesity in people with intellectual disabilities: analysis by age groups - Ferrero Hernández, Paloma.; Farías Valenzuela, Claudio Ítalo.; Ferrari, Gerson; Espoz Lazo, Sebastián.; Álvarez Arangua, Sebastián.; Valdivia Moral, Pedro. (JIDRE, 2023)
Background: The prevalence of overweight/obesity has been increasing globally and in people with Intellectual Disabilities (IDs), this problem is exacerbated even more, which added to a low physical condition that contributes to the deterioration of functionality and increases the risk of developing chronic diseases in the course of life. Therefore, the aim of this study was to establish cut-off points for levels of isometric handgrip and low limb explosive strength in children, adolescents and adults, which identify overweight/obesity in people with IDs and their respective associations. Methods: The sample was made up of 131 individuals with IDs, belonging to four special and community educational centres in the city of Santiago, Chile. Body mass index (BMI) and waist-to-height ratio (WHR) were used as indicators of overweight/obesity. Handgrip strength was used as a measure of isometric strength, and countermovement jump was used as a measure of low limb explosive strength. For the comparison of variables by age group, the analysis of Ancova, Kruskal–Wallis and chi-square tests were used. The total area under the receiver operating characteristic curve of isometric handgrip and low limb explosive strength was identified as an indicator of overweight/obesity according to age groups. A logistic regression model was used to quantify the effect that strength categories below the cut-off point have on the risk of overweight and obesity. Results: Significant differences were observed between the age groups for body weight, height, BMI and WHR, as well as in the levels of absolute handgrip strength and vertical jump with countermovement (P ≤ 0.05). Children showed the lowest cut-off points for absolute and relative strength. The adolescent group showed the highest cut-off points for relative strength and countermovement jump and adults showed the highest value for absolute strength as indicators of overweight/obesity. Different associations between cut-off points with BMI and WHR were found. Conclusions: Adolescents showed the highest cut-off point for relative strength and countermovement jump, and adults showed the highest value for absolute strength, according to overweight/obesity indicators (BMI and WHR). It is suggested to adjust resistance training programmes according to age categories for the prevention of overweight/obesity in people with IDs.
Keywords: Countermovement jump; Functional capacity; Handgrip strength; Intellectual disability; Fuerza muscular; Obesidad